2019
DOI: 10.3389/fimmu.2019.01384
|View full text |Cite
|
Sign up to set email alerts
|

The Rheumatoid Arthritis Risk Gene AIRE Is Induced by Cytokines in Fibroblast-Like Synoviocytes and Augments the Pro-inflammatory Response

Abstract: The autoimmune regulator AIRE controls the negative selection of self-reactive T-cells as well as the induction of regulatory T-cells in the thymus by mastering the transcription and presentation of tissue restricted antigens (TRAs) in thymic cells. However, extrathymic AIRE expression of hitherto unknown clinical significance has also been reported. Genetic polymorphisms of AIRE have been associated with rheumatoid arthritis (RA), but no specific disease-mediating mechanism has been ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The pathogenic role of IFN-c as an upstream regulator in RA synovium has also been shown by meta-analysis across datasets of gene expression microarray [24]. Another recent study by Bergstr€ om et al [25] has demonstrated a novel role for the autoimmune regulator (AIRE), a master regulator of T cell tolerance in the thymus, in IFN-c signature in synovial fibroblasts. By RNA sequencing, they identified 3,492 differentially expressed genes, including AIRE, in synovial fibroblasts following treatment with TNF-a and IL-1b.…”
Section: Ifn-c In Synovial Biologymentioning
confidence: 89%
“…The pathogenic role of IFN-c as an upstream regulator in RA synovium has also been shown by meta-analysis across datasets of gene expression microarray [24]. Another recent study by Bergstr€ om et al [25] has demonstrated a novel role for the autoimmune regulator (AIRE), a master regulator of T cell tolerance in the thymus, in IFN-c signature in synovial fibroblasts. By RNA sequencing, they identified 3,492 differentially expressed genes, including AIRE, in synovial fibroblasts following treatment with TNF-a and IL-1b.…”
Section: Ifn-c In Synovial Biologymentioning
confidence: 89%
“…In this context, fibroblast-like synoviocytes (FLSs) are increasingly recognized as key effector cells. 3 The activated FLSs are hyperproliferative and resistant to apoptosis with an increased capacity for migration, causing pannus formation and destruction of joint cartilage. Production of inflammatory factors such as tumor necrosis factor a (TNF-a) and interleukin 17 (IL-17), chemokines, and matrix-degrading molecules by FLSs contributes to their invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…RNA sequencing revealed that AIRE did not induce PTAs in FLS, but stimulates pro-inflammatory cytokine and chemokine secretion associated with RA development. AIRE expression was hardly detected on mRNA level in unstimulated RA FLS, but largely increased and detected at protein level after TNFα and IL1β stimulation (64). Single-cell RNA sequencing on RA FLS showed a putative subpopulation of CD90 + HLA-DR high FLS expanded in the sublining of RA synovium.…”
Section: Insights From Synovium During Early Ra Developmentmentioning
confidence: 90%
“…Similar to stromal cells in the LN, FLS create a pro-survival and anti-apoptotic microenvironment in the synovium by secreting cytokines and chemokines that support the survival of immune cells supporting inflammation (62,63). AIRE was recently identified as a cytokine-induced RA-risk gene in RA FLS (64). RNA sequencing revealed that AIRE did not induce PTAs in FLS, but stimulates pro-inflammatory cytokine and chemokine secretion associated with RA development.…”
Section: Insights From Synovium During Early Ra Developmentmentioning
confidence: 99%